Investigation of Driving Forces of Energy Consumption in EU 28 Countries - Obadi, Saleh Mothana; KorÄek, Matej (International Journal of Energy Economics and Policy, 2015)
This paper aims to analyze drivers of energy consumption in EU in recent period and identify the role of energy efficiency in it. We analyzed energy consumption using LMDI decomposition technique on three different levels of data aggregation for EU 28 countries in pre-crisis period (2004-2008) and crisis period (2008-2012). Our paper challenged the view that recent decline in energy consumption is caused by economic slowdown as improvements in energy intensity EU countries seems to be slowing down. We conclude that intensity effect was the major factor influencing energy consumption, while the contribution of activity effect representing the performance of economy was of less importance. The impact of structural effect was only of minor magnitude but interestingly has larger influence during the period of oil prices surge than in period of high oil prices. Our evidence also suggests that structural changes of economies towards service sector will likely lead to lower improvements in energy efficiencies. Keywords: Energy efficiency; energy consumption, EU; energy intensity JEL Classifications: O13; Q2; Q 3, Q 4